Phytochemical screening and antioxidant activity of diff erent bee honeys - P. Mary Ukkuru, V. Krishnasree (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The present study aimed at elucidating the protective role of honeys produced by the five bee species that prevail in Kerala namely, Apis cerana indica F., Apis mellifera L., Apis dorsata F., Apis florea F. and Trigona iridipennis S. in their raw and processed form against oxidative stress and free radicals. The major phytochemicals screened were polyphenols, flavonoids, and flavonols. The antioxidant potency of the honeys was analyzed using in vitro antioxidant assays namely, 2, 2 diphenyl-1-picrylhydrazyl assay and nitric oxide scavenging assay. The results indicated that the honeys in pure form were having a higher rate of antioxidant activity compared to processed honeys as processing reduce the thermolabile phytochemicals.